(untitled) (The International Journal for Scientific Research, 2025)
This study undertakes a comparative examination of two foundational works in the science of Tajweed: Al-Tahdid fi Al-Itqan wa Al-Tajweed by Abu Amr Uthman bin Saeed Al-Dani (444 AH) and Al-Mowdah fi Al-Tajweed by Abdul-Wahhab bin Muhammad Al-Qurtubi (461 AH). The comparison focuses on the agreement and divergence in methodology and style, highlighting scientific characteristics that distinguish each work and their lasting influence on subsequent scholars in Qur’anic sciences, recitations, and Tajweed. The research employs the inductive and descriptive-analytical approaches to uncover intellectual development of Tajweed as a discipline, emphasizing the value of these texts as authoritative references and pillars in preserving and documenting its principles. The study concludes that Al-Dani and Al-Qurtubi played a decisive role in codifying Tajweed, laying down rules that shaped later scholarship and practice. Accordingly, the research stresses the necessity of returning to early classical works, combining their careful study with continuous practice and recitation under expert guidance. Furthermore, the writings of Dr. Ghanem Qaddouri Al-Hamad are noted as among the most reliable modern references in this field.